Vertical Changes in the Flux of Atmospheric Nitrate From a Forest Canopy to the Surface Soil Based on Δ17O Values. Issue 4 (6th April 2021) - Inoue, Takahiro; Nakagawa, Fumiko; Shibata, Hideaki; Tsunogai, Urumu
Abstract: To better understand the factors that control N retention and N export in forested watersheds, it is necessary to understand the relationships among atmospheric nitrogen (N) deposition, internal N cycling within plant‐soil systems, and N leaching. The relative contributions of atmospheric nitrate (NO3 − atm ) and remineralized nitrate produced by microbial nitrification to total nitrate (NO3 − ) in stream water have been investigated in many studies. However, the dynamics of these two types of NO3 − from the forest canopy to the soil are not well understood. Therefore, we determined the changes in the NO3 − flux and the 17 O excess (Δ 17 O) of NO3 −, a robust tracer of NO3 − atm, from bulk deposition to the soil water beneath oak and spruce trees as well as dwarf bamboo‐dominated canopy gaps in a natural coniferous‐broadleaved mixed forest in northern Japan. The Δ 17 O values in NO3 − dramatically decreased after passing through the forest floor, indicating that the dominant source of NO3 − leaching is nitrification in the forest floor. In contrast, a large decrease in NO3 − atm flux was observed between bulk deposition and throughfall, especially for oak and spruce, suggesting that the forest canopy is an important sink for deposited NO3 − atm . The retention of NO3 − atm by the canopy was higher for oak (86.3 ± 10.1%) and spruce (87.7 ± 8.8%) than for Sasa in the canopy gap (49.9 ± 26.6%). Our study demonstrated that the Δ 17 O value of NO3 − is a promising tool for quantifying the atmospheric nitrate dynamics in complex forest N cycling. Plain Language Summary: Excess atmospheric nitrogen (N) deposition in forests can increase N leaching to streams, which may induce eutrophication in downstream ecosystems. Therefore, understanding the relationships among atmospheric N deposition, internal N cycling within plant‐soil systems, and N leaching is necessary to better understand the factors that control N export in forested watersheds. Triple oxygen isotopes of nitrate (NO3 − ) are useful tracers of atmospheric nitrate (NO3 − atm ). Therefore, we examined the proportion of NO3 − atm to total NO3 − and the flux of NO3 − atm in waters that pass through forest canopies and surface soils in a natural coniferous‐broadleaved mixed forest by using triple oxygen isotopes of NO3 − . The results showed that the dominant source of NO3 − in the water samples switched from NO3 − atm to NO3 − produced by nitrification when the water passed through the forest floor. This is in line with previous findings. In contrast, the NO3 − atm flux largely decreased from rainfall to throughfall, especially for oak and spruce, suggesting that the forest canopy is an important sink for deposited NO3 − atm . Our study demonstrated that the Δ 17 O value of NO3 − is a promising tool for quantifying the atmospheric nitrate dynamics in complex forest N cycling. Key Points: The vertical profiles of the proportion of atmospheric NO3 − to total NO3 − were different from those of atmospheric NO3 − flux The forest canopy retained a large portion of the deposited atmospheric NO3 − The retention rates of atmospheric NO3 − were different among different canopy types